Pentingnya Kerjasama Antara Sekolah Dan Orang Tua Dalam Meningkatkan Prestasi Siswa - Nur Cahaya Daulay; Sahbuki Ritonga (Jurnal Zeniusi, 2024)
This research aims to examine the application of understanding student characteristics to mitigate unwanted behaviour at Al Yusra Abadi Tahfiz School. The employed research method is qualitative, utilising data collection approaches such as literature review, observation, and interviews. The research findings indicate that the implementation of educational techniques derived from the Quran and Hadith, including memorisation, talaqqi, and discourse, positively influences the character development of students. Furthermore, the pesantren setting and the profound interaction between students and teachers significantly contribute to the development of discipline, responsibility, and virtuous character. Factors facilitating research implementation encompass the provision of ample learning opportunities and the endorsement of proficient educators. Simultaneously, there are other constraining factors, including insufficient student motivation and difficulties in regularly applying pedagogical methods. The effective execution of the Al Yusra Abadi Tahfiz program can mitigate negative behaviour and elevate the moral standards of students, rendering them virtuous and advantageous to society.